Reading Times" for Reciting the Qur'an from the Treatise "Reciting the Qur'an" by Imam Abu Sa'id al-Khadimi: A(d. 1176 AH) Study and An Investigation - Abdullah Najm Abdullah, (Islamic Sciences Journal, 2025)
This research is titled: "Times of Reading" for Reciting the Qur'an from "The Epistle on the Recitation of the Qur'an" by Imam Abu Sa'id al-Khadimi (d. 1176 AH) (A Study and Verification(. In the academic section of this research, I discuss Imam al-Khadimi's personal and academic life, concluding with the researcher's methodology and extracts from the manuscript. The second section is devoted to the verified text, as intended by the author. It discusses the best times for reading the Qur'an, which the reader should be aware of when beginning to recite the Glorious Qur'an.